Analysis of phenolic and flavonoid compounds in Malaysia propolis extracts by LC-Q-TOFMS - Mokhtar, Siti Umairah; Mohamed Shajahan, Fahmeeda Parvin; Sidik, Siti Sarah; Mat Zuki, Mohd Farhanuddin Irfan (2021)
Propolis is a natural bee product which is resinous sticky wax (bee glue) that synthesized by the stingless bees from the mixtures of exudates of plants and bee enzymes. The chemical compounds of propolis mainly consists of phenolic acids and flavonoids. Since propolis has been consumed for ages as a traditional medicine and research on the Malaysia propolis is still lacking, this study was conducted. Therefore, propolis was 1 extracted by Soxhlet Extraction (using two different solvents) and 2 determined their chemical profiling by using LC-QTOFMS which 3 focusing on potential API that can be used in pharmaceutical product.